Indywidualizm versus wspólnotowość - Karnowska, Danuta (Political Preferences, 2011)
After 1989, the Polish political scene clashed two traditions: individualism and commu- nity. They were a reflection of social trends and habits, whereas for the political parties beca- me the axis around which were decided the main dilemmas of the political system, economy and cultural sphere of the society. Dilemmas of reconciling individualism with community trends were consistent with the presence of Catholic values in society, traditions and political culture. Along with the consolidation of democracy in Poland, became the determinant of political views and atti- tudes, thereby affecting the socio-political divisions in Poland.